The Complex Interplay Between Depression/Anxiety and Executive Functioning: Insights From the ECAS in a Large ALS Population - Carelli, Laura; Solca, Federica; Faini, Andrea; Madotto, Fabiana; Lafronza, Annalisa; Monti, Alessia; Zago, Stefano; Doretti, Alberto; Ciammola, Andrea; Ticozzi, Nicola; Silani, Vincenzo; Poletti, Barbara (Frontiers in Psychology, 2018)
Introduction: The observed association between depressive symptoms and cognitive performances has not been previously clarified in patients with Amyotrophic Lateral Sclerosis (pALS). In fact, the use of cognitive measures often not accommodating for motor disability has led to heterogeneous and not conclusive findings about this issue. The aim of the present study was to evaluate the relationship between cognitive and depressive/anxiety symptoms by means of the recently developed Edinburgh Cognitive and Behavioural ALS Screen (ECAS), a brief assessment specifically designed for pALS. Methods: Sample included 168 pALS (114 males, 54 females); they were administered two standard cognitive screening tools (FAB; MoCA) and the ECAS, assessing different cognitive domains, including ALS-specific tasks (executive functions, verbal fluency and language tests) and ALS Non-specific subtests (memory and visuospatial tests). Two psychological questionnaires for depression and anxiety (BDI; STAI/Y) were also administered to patients. Pearson’s correlation coefficient was used to assess the degree of association between cognitive and psychological measures. Results: Depression assessment negatively correlated with the ECAS, more significantly with regard to the executive functions subdomain. In particular, Sentence Completion and Social Cognition subscores were negatively associated with depression levels measured by BDI total score and Somatic-Performance symptoms subscore. Conversely, no significant correlations were observed between depression level and cognitive functions as measured by traditional screening tools for frontal abilities (FAB) and global cognition (MoCA) assessment. Finally, no significant correlations were observed between state/trait anxiety and the ECAS. Discussion and conclusions: This represents the first study focusing on the relationship between cognitive and psychological components in pALS by means of the ECAS, the current gold standard for ALS cognitive-behavioural assessment. If confirmed by further investigations, the observed association between depression and executive functionssuggests the need for a careful screening and treatment of depression, to avoid overestimation of cognitive involvement and possibly improve cognitive performances in ALS.